Modelo constructivista para el anlisis y prevencin del pandillaje - Vasquez Saldaa, Marita Marleny (2019)
The session titles Constructivist model for gang analysis and prevention this was carried out as part of the Person, Family and Human relationships course for secondary third grade students from the San Nicolas education institute._x000D_ The session purpose is impart, analyse and propose alternatives of solution to prevent gangs. This has been obtained by using a constructivist model that conceives learning as result off process of personal and collective construction .